The Role of Neuromuscular Monitorisation in the Use of Muscle Relaxants [Kas Gevşetici Ajan Kullaniminda, Sinir Kas Kavşak Monitörizasyonunun Rolü] - (:unkn) unknown (My University, 2003)
In this study; our goal was to find out if there was any difference in consumption of vecuronium bromide depending on whether a peripheral nerve stimulation was used or not. Anesthesia reports of 251 patients, ASA physical status I-II, 20-60 yr old, who were underwent peripheral elective surgery, vecuronium bromide used for muscle relaxation, isoflurane or sevoflurane used as an inhalational anesthetic, and endotracheal intubation or laryngeal mask used for airway providing method were analysed retrospectively. Patients were divided into 2 main groups: Group I (n=104); peripheral nerve stimulation used, Group II (n=147); peripheral nerve stimulation not used. Both groups were also divided into 2 subgroups to research the effect of inhalational anesthetics (isoflurane and sevoflurane) and airway providing methods (endotracheal intubation and laringeal mask airway) on vecuronium bromide consumption. Consumption rate of vecuronium bromide was calculated as μg kg-1 dk-1 min and, both groups and subgroups were compared according to the consumption of vecuronium bromide statistically. As a result; vecuronium bromide consumption rate was found significantly higher when peripheral nerve stimulation used (1.38±0.18 μg kg-1 min-1) compared to not used (1.09±0.23 μg kg-1 min-1) (p<0.05). There was no significant differance in vecuronium consuption rate between subgroups (p<0.05). We concluded that usage of a peripheral nerve stimulation might increase vecuronium consumption rate when absolute muscle relaxation is not required.
Keywords: Isoflurane; Peripheral nerve stimulator; Sevoflurane; Vecuronium bromide